Experimental and Evaluation of Flexural Capacity in Voided RC Slab with Internal Truncated Pyramid Shaped Voids - พวงเรืองศรี, ชัชวาล; ลิมปนิลชาติ, พรเพ็ญ (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
Truncated Pyramid Shaped (TPS) voided former is an alternative voided shape embedded inside the reinforced concrete slab to reduce concrete quantity. The main purposes of this study were to investigate the one directional flexural behavior of TPS voided slab through the four-point bending test and compared the experimental results with the evaluation of flexural capacity. Two TPS voided slabs with dimension of 2700x1500 mm2 and different thickness of 260 mm and 300 mm were subjected to the loading test. During the loading test, the results of load, deflection and strains in concrete and steel bars were recorded to observe their relevant behaviors. Consequently, the evaluation method for flexural capacity of the TPS voided slab was proposed by using the fundamental flexural analysis. Finally, the loading capacities from both specimens showed good agreement results between the experiment and evaluation method with an accuracy of up to 94.93%.